Manajemen Talenta dan Manajemen Resiko Pengaruhnya Terhadap Kinerja Karyawan Perusahaan Petikemas di Surabaya - Dyah Agustin Widhi Yanti; Mursidi Mursidi (Journal of Business and Economics Research (JBE), 2022)
Human resources who are professional and have high dynamic and competitive competence in facing the challenges of the 21st century are needed in organizations. Key competitive factor in creating an organization that has an advantage is the HR development program. Companies or organizations either government or private need employees who have certain talents so that the company can develop. Everyone has different talents from others, so management around good talent is needed to overcome the career problems of employees in the company. The management of talented human resources is very necessary, in order to detect, develop, and use their talents to achieve personal and organizational goals more optimally. Variables in this study are: talent management, risk management and individual performance. The purpose of this study is: (1) analyzing the influence of talent management on employee performance (2). analyze the influence of risk management on the performance of employees who take research locations at PT. Petikemas Surabaya. The results showed that there is a significant influence between talent management and risk management both partially and simultaneously on performance so that all hioptesis in this study can be proven acceptable.